THE ANALYSIS OF PRODUCTIVE ASSETS QUALITY ON BANK HEALTH RATING OF COMMERCIAL BANKS IN INDONESIA - Angrita Denziana; Haninun -; Erwin Octavianto (Proceeding International Conference on Information Technology and Business, 2015)
The purpose of this study was to analyze the effect ofthe quality level of the productive assets of the bank. Indaily activities functioning bank intermediationinstitution that is as an institution that gathers anddistributes funds from surplus unit to deficit unit.Channeling funds into bank unit deficit is done througha wide range of credit products offered both to creditused to personally or company. The owned credit bankit’s assets productive or assets generate but not justcredit as the only productive asset owned by the bankthere are other productive assets owned by the bank thatthe bank funds placement with other banks, securitiesowned, investment capital, acceptance speeches arebills, bills and derivatives, as well as administrativeaccount transactions.KEYWORDS: Productive Assets Quality, Bank HealthLevel